Simulation of the joining process of graded hardened multi-range capable rivets - Holtkamp, Pia Katharina; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Materials Research Proceedings)
Abstract. The versatile self-pierce riveting (V-SPR) is a further development of semi-tubular self-pierce riveting. V-SPR enables adaptation to changing boundary conditions, such as a change in the material thickness combination, without varying the rivet die combination due to increased punch actuation and the use of multi-range capable rivets [1]. The inner punch first sets the rivet. The outer punch then forms the rivet head to the respective sheet thickness. For this, the rivet requires a hard shank and a ductile rivet head, which is achieved by an inductive local hardening process [2]. Until now, the joint formation of rivets with graded hardness profile has been challenging to estimate in the FEM simulation due to the inhomogeneous material conditions in the rivet. In this study, a method capable of reproducing the experimentally determined hardness levels of rivets in detail is shown. This FE model enables the realistic modelling of the mechanical properties of the rivet on the basis of the hardness profile in order to predict the correct deformation processes and stresses during the riveting process. First, the detailed experimental hardness mapping of the locally heat-treated rivets is transferred into the FE model. The FEM material model can predict the local strength of the rivet based on hardness by scaling the flow curves. To estimate the predictive capability of the FEM model, the joint formation of rivets with different graded hardness profiles is compared experimentally and simulative. Based on the validated model, the influence of different rivet hardness profiles on the joint formation is analysed numerically. By adapting the material model, a high level of correlation between the experiment's joint formation and the simulation can be achieved.

Integration of multiple-linear and tumbling kinematics into self-piercing riveting - Holtkamp, Pia Katharina; Wituschek, Simon; Lechner, Michael; Meschut, Gerson (MATEC Web of Conferences)
Conventional mechanical joining processes are typically rigid in their tool systems and can only react to changing process and disturbance variables to a limited extent. At the same time, various industries are increasingly trending towards multi-material systems consisting of parts with varying geometric and mechanical properties. Due to the varying properties, rigid mechanical joining processes require sampling procedures and periodic changes of tool components or auxiliary joining parts. Consequently, research is focusing on versatile mechanical joining processes that allow increased control by modifying the process parameters. Two processes based on self-piercing riveting can achieve a significant increase in process influence possibilities through a multi-linear actuator as versatile self-piercing riveting (V-SPR) and a tumbling superimposed actuator as tumbling self-piercing riveting (T-SPR). Initial research into V-SPR has shown that this process can be used to achieve a higher variation in overall package thickness by adapting the rivet geometry and using multiple linear actuators. The T-SPR process also enables increased material flow control by means of targeted compression of the rivet using the tumbling actuator, thereby extending the range of joints that can be manufactured. Based on these two processes, a combination of the two mechanisms of action is to be developed.

Non-destructive testing in versatile joining processes - Lechner, M.; Borgert, Thomas; Busch, Matthias; Harms, A.; Holtkamp, Pia Katharina; Römisch, D.; Wituschek, Simon; Kappe, Fabian (Materials Research Proceedings)
Abstract. Mechanical joints are traditionally analyzed through destructive micrograph analysis, which may compromise internal geometry and morphology, as evidenced by radial cracks in semi-tubular self-pierce riveting. In contrast, industrial X-ray computed tomography (XCT) offers a non-destructive method for component diagnosis, providing volumetric insights without damaging the sample and enabling dimensional measurement. The DFG-funded Collaborative Research Center TRR 285 is exploring XCT's application in assessing mechanical joinability across various joining processes and materials, particularly in multi-material systems like steel-aluminum joints. XCT faces challenges in accurately capturing multi-material compositions, leading to artifacts that complicate interface detection. This research aims to validate XCT for joint investigations, yielding quantitative characteristics that surpass those from traditional micrograph analysis.

Machine learning of continuous and discrete variational ODEs with convergence guarantee and uncertainty quantification - Offen, Christian (Mathematics of Computation)
The article introduces a method to learn dynamical systems that are governed by Euler–Lagrange equations from data. The method is based on Gaussian process regression and identifies continuous or discrete Lagrangians and is, therefore, structure preserving by design. A rigorous proof of convergence as the distance between observation data points converges to zero and lower bounds for convergence rates are provided. Next to convergence guarantees, the method allows for quantification of model uncertainty, which can provide a basis of adaptive sampling techniques. We provide efficient uncertainty quantification of any observable that is linear in the Lagrangian, including of Hamiltonian functions (energy) and symplectic structures, which is of interest in the context of system identification. The article overcomes major practical and theoretical difficulties related to the ill-posedness of the identification task of (discrete) Lagrangians through a careful design of geometric regularisation strategies and through an exploit of a relation to convex minimisation problems in reproducing kernel Hilbert spaces.

PHOENIX – Paderborn highly optimized and energy efficient solver for two-dimensional nonlinear Schrödinger equations with integrated extensions - Wingenbach, Jan; Bauch, David; Ma, Xuekai; Schade, Robert; Plessl, Christian; Schumacher, Stefan (Computer Physics Communications)
In this work, we introduce PHOENIX, a highly optimized explicit open-source solver for two-dimensional nonlinear Schrödinger equations with extensions. The nonlinear Schrödinger equation and its extensions (Gross-Pitaevskii equation) are widely studied to model and analyze complex phenomena in fields such as optics, condensed matter physics, fluid dynamics, and plasma physics. It serves as a powerful tool for understanding nonlinear wave dynamics, soliton formation, and the interplay between nonlinearity, dispersion, and diffraction. By extending the nonlinear Schrödinger equation, various physical effects such as non-Hermiticity, spin-orbit interaction, and quantum optical aspects can be incorporated. PHOENIX is designed to accommodate a wide range of applications by a straightforward extendability without the need for user knowledge of computing architectures or performance optimization. The high performance and power efficiency of PHOENIX are demonstrated on a wide range of entry-class to high-end consumer and high-performance computing GPUs and CPUs. Compared to a more conventional MATLAB implementation, a speedup of up to three orders of magnitude and energy savings of up to 99.8% are achieved. The performance is compared to a performance model showing that PHOENIX performs close to the relevant performance bounds in many situations. The possibilities of PHOENIX are demonstrated with a range of practical examples from the realm of nonlinear (quantum) photonics in planar microresonators with active media including exciton-polariton condensates. Examples range from solutions on very large grids, the use of local optimization algorithms, to Monte Carlo ensemble evolutions with quantum noise enabling the tomography of the system's quantum state.

Konzeptionierung eines digitalen Wissensmanagementsystems für die zivile Gefahrenabwehr am Beispiel der Feuerwehr - Schultz, Andreas Maximilian
Wissensmanagement ist im unternehmerischen Kontext ein etabliertes Feld der Forschung und Praxis, das auf die Verbesserung von Effizienz und Wettbewerbsfähigkeit abzielt. In den Organisationen der zivilen Gefahrenabwehr hingegen gibt es erhebliche Defizite bei der Erfassung und Weitergabe von Wissen, obwohl auch hier große Abhängigkeiten vom Erfahrungswissen bestehen. Diese Arbeit analysiert am Beispiel der Feuerwehr die Gründe für diese Diskrepanz und entwickelt ein Konzept, das das Wissensmanagement im Feuerwehrwesen nachhaltig verankern soll. Eine deutschlandweite Umfrage mit 577 Einsatzkräften ergab, dass eine digitale Verwaltungsunterstützung bereits verbreitet ist, das Wissen jedoch vornehmlich per E-Mail, Chat, mündlich oder per Aushang verteilt wird. Die Teilnehmenden wünschen sich eine Lösung für das Wissensmanagement, die im Einsatz, bei Aus- und Weiterbildung sowie der Verwaltungsarbeit unterstützt. Auf der Umfrage und einer systematischen Literaturrecherche aufbauend, wurde der Handlungsbedarf identifiziert. Darauf basieren die Ableitung der Anwendungsbereiche sowie Rahmenbedingungen, welche sich in den Anforderungen an ein Wissensmanagementsystem widerspiegeln. Das Umsetzungskonzept beschreibt die Systemarchitektur der Lösung, die auf einem open-source Wiki mit passenden Erweiterungen beruht. Zentrales Element ist die Möglichkeit zum Austausch von Wissen über Organisationsgrenzen. Abgeschlossen wird die Arbeit mit der Demonstration und Evaluation der Lösung.

Can bioelectrical impedance analysis be used to identify water loading in patients with anorexia nervosa?- Implications from experimental measurements in young, healthy, and normal weight women. - Knoll-Pientka, N; Schils, D; Pasternak, K; Czarnetzky, S; Jansen, C; Gradl-Dietsch, G; Seitz, J; Skoda, EM; Libuda, Lars; Schweda, A; Teufel, M (J Eat Disord)

Soft and Constrained Hypertree Width - Lanzinger, Matthias; Okulmus, Cem; Pichler, Reinhard; Selzer, Alexander; Gottlob, Georg (Proceedings of the ACM on Management of Data)
Hypertree decompositions provide a way to evaluate Conjunctive Queries (CQs) in polynomial time, where the exponent of this polynomial is determined by the width of the decomposition. In theory, the goal of efficient CQ evaluation therefore has to be a minimisation of the width. However, in practical settings, it turns out that there are also other properties of a decomposition that influence the performance of query evaluation. It is therefore of interest to restrict the computation of decompositions by constraints and to guide this computation by preferences. To this end, we propose a novel framework based on candidate tree decompositions, which allows us to introduce soft hypertree width (shw). This width measure is a relaxation of hypertree width (hw); it is never greater than hw and, in some cases, shw may actually be lower than hw. Most importantly, shw preserves the tractability of deciding if a given CQ is below some fixed bound, while offering more algorithmic flexibility. In particular, it provides a natural way to incorporate preferences and constraints into the computation of decompositions. A prototype implementation and preliminary experiments confirm that this novel framework can indeed have a practical impact on query evaluation.

Thermo-Hydraulic Performance of Pillow-Plate Heat Exchangers with Streamlined Secondary Structures: A Numerical Analysis - Afsahnoudeh, Reza; Riese, Julia; Kenig, Eugeny Y. (Systems and Control Transactions)
Pillow-plate heat exchangers (PPHEs) represent a viable alternative to conventional shell-and-tube and plate heat exchangers. The waviness of their channels intensifies fluid mixing in the boundary layers and facilitates heat transfer. Applying secondary surface structuring can further enhance the overall thermo-hydraulic performance of PPHEs, thus increasing their competitiveness against conventional heat exchangers. In this work, streamlined secondary structures applied on the PPHE surface were studied numerically to explore their potential in enhancing near-wall fluid mixing. Computational fluid dynamics (CFD) simulations of single-phase turbulent flow in the inner PPHE channel were performed and pressure drop, heat transfer coefficients, and overall thermo-hydraulic efficiency were determined. The simulation results clearly demonstrate a favourable influence of secondary structuring on the heat transfer performance of PPHEs.

A Data-Driven Conceptual Approach to Heat Pump Sizing in Chemical Processes with Fluctuating Heat Supply and Demand - Hochhaus, Thorben; Wloch, Johannes; Grünewald, Marcus; Riese, Julia (Systems and Control Transactions)
Heat pumps play a crucial role in decarbonizing the chemical industry. The integration and sizing of heat pumps in chemical processes is a challenging task in multi-product chemical processes due to the fluctuating waste heat supply and heat demand. Integrating heat pumps may require a retrofit of the utility system. Mathematical optimization is a useful tool to tackle this challenge by enabling the analysis of correlation between relevant system parameters and equipment sizing. This study demonstrates the utilization of mathematical optimization and parameter studies for utility system equipment sizing addressing fluctuating heat supply and demand profiles.

Explorative Datenanalyse in der Schule – Analyse der Mediennutzung von Jugendlichen mit den YOU‑PB Daten - Podworny, Susanne; Fleischer, Yannik; Biehler, Rolf (Stochastik in der Schule)

On the association scheme of perfect matchings and their designs - Klawuhn, Lukas-André Dominik; Bamberg, John
We investigate generalisations of 1-factorisations and hyperfactorisations of the complete graph $K_{2n}$. We show that they are special subsets of the association scheme obtained from the Gelfand pair $(S_{2n},S_2 \wr S_n)$. This unifies and extends results by Cameron (1976) and gives rise to new existence and non-existence results. Our methods involve working in the group algebra $\mathbb{C}[S_{2n}]$ and using the representation theory of $S_{2n}$.

Towards Practicable Algorithms for Rewriting Graph Queries Beyond DL-Lite - Löhnert, Bianca; Augsten, Nikolaus; Okulmus, Cem; Ortiz, Magdalena (The Semantic Web - 22nd European Semantic Web Conference, ESWC 2025, Portoroz, Slovenia, June 1-5, 2025, Proceedings, Part I)
Despite the advantages that the virtual knowledge graph paradigm has brought to many application domains, state-of-the-art systems still do not support popular graph database management systems like Neo4j. Their query rewriting algorithms focus on languages like conjunctive queries and their unions, which were developed for relational data and are poorly suited for graph data. Moreover, they also limit the expressiveness of the ontology languages that admit rewritings, restricting them to those that enjoy the so-called FO-rewritability property. Rewritings have thus focused on the DL-Lite family of Description Logics. In this paper, we propose a technique for rewriting a family of navigational queries for a suitably tailored fragment of ELHI. Leveraging navigational features in the target query language, we can include some widely-used axiom shapes not supported by DL-Lite. We implemented a proof-of-concept prototype that rewrites into Cypher queries, and tested it on a real-world cognitive neuroscience use case with promising results.
Keywords: Ontology-based Data Access; Property Graphs; Navigational Queries

Evaluation of piezoelectric micromachined ultrasonic transducers (PMUT) for the broadband detection of ultrasonic elastic waves - Zeipert, Henning; Claes, Leander; Stoeckel, Chris; Mulay, Shubham; Henning, Bernd

String Partition for Building Long BWTs - Adler, Enno; Böttcher, Stefan; Hartel, Rita (2025 Data Compression Conference (DCC))

Cost-efficient folding of functionalized DNA origami nanostructures via staple recycling - Tomm, Emilia; Grundmeier, Guido; Keller, Adrian (Nanoscale)
DNA origami nanostructures are powerful molecular tools for the controlled arrangement of functional molecules and thus have important applications in biomedicine, sensing, and materials science. The fabrication of DNA origami...

ReVEAL model and its application to revealing viewpoints on educational approaches to learning about data and AI - Höper, Lukas; Schulte, Carsten (Computer Science Education)

Ultrasonic phased array interface using programmable I/O and microprocessor clock synchronisation - Nellius, Tom; Henne, Kevin; Hartinger, Maximilian; Meihost, Lars; Hetkämper, Tim; Zeipert, Henning; Claes, Leander; Henning, Bernd

Zwischen Verstehensillusion und Wissenserwerb - Kulgemeyer, Christoph; Hörnlein, Madeleine (Plus Lucis)

#Fitspiration als Teil der juvenilen Bewegungskultur im Sportunterricht. Ergebnisse einer qualitativen Interviewstudie mit Sportlehrkräften - Korte, Johanna; Grimminger-Seidensticker, Elke (Zeitschrift für sportpädagogische Forschung)
Die Auseinandersetzung mit Fitnessinhalten in sozialen Medien nimmt für Jugendliche eine bedeutende Rolle ein. Diese Inhalte können einerseits als Motivation für körperliche Aktivität dienen, andererseits aber auch negative Auswirkungen auf das Körperbild haben. Deswegen spielen Sportlehrkräfte in diesem Zusammenhang eine entscheidende Rolle bei der Vermittlung von Medienkompetenz. Um ihre Perspektiven zu dieser Herausforderung besser zu verstehen, wurden leitfadengestützte Interviews mit N=17 Sportlehrkräften unterschiedlicher Schulformen durchgeführt. Die Ergebnisse zeigen, dass die meisten Lehrkräfte nicht genau wissen, wie ihre Schüler:innen Fitnessinhalte in sozialen Medien nutzen, obgleich sie eine gewisse Relevanz darin für Jugendliche sehen. Die Sportlehrkräfte unterscheiden sich in der Ansicht darüber, ob und wie diese Thematik im Sportunterricht behandelt werden sollte. Nur wenige Lehrkräfte integrieren sie bereits in ihren Unterricht, während andere dies für nicht sinnvoll oder schwer umsetzbar halten. Diese vielfältigen Perspektiven verdeutlichen die Komplexität der Medienbildung im Sportunterricht und die Notwendigkeit, Medienbildung als Thema in der Lehrer:innenbildung aufzugreifen.